Examining Mandatory Audit Firm Rotation and Audit Quality in South Africa: Practitioner and Academic Perspectives - Aminu, Munkaila; Nomlala, Bomi Cyril; Baldavoo, Kiran (International Journal of Economics and Financial Issues, 2024)
In this study, we examined the perceptions of practitioners and academics perspectives about the impact of mandatory audit firm rotation (MAFR) on audit quality (AQ) in South Africa within the province of KwaZulu-Natal. The paper considered the position of the European Union (EU) and the South African Independent Regulatory Body for Auditors (IRBA) regarding its policy shift on MAFR. The study examined the logical connection between MAFR and AQ. This was through the opinion of 101 practitioners and academics gathered from Tier 2 audit firms and two public institutions about the readiness of the rule in South Africa’s jurisdiction. We utilised a quantitative research method through descriptive statistics to understand the influence of the policy on AQ. Opinions of audit experts through closed-ended questionnaires were a distinct feature of our research, while analysis of the descriptive study was on the usage of feedback from respondents. Results from the data analysis presented provided a general overview of respondents’ opinions on the rule. Affirming our research aim, data from the majority of respondents agreed that the policy would strengthen AQ but maintained that the results of the additional imposition of cost could be worse. While this paper contributes to the existing literature on MAFR and AQ, it recommends that further research should concentrate on pre and post-implementation of the policy employing views from registered auditors and academics from different provinces in South Africa to measure the policy effects of the rule on AQ.